Mutsu Munemitsu and his time - Okazaki, Hisahiko 1930-2014; Noda, Makito (Tokyo Japan Publishing Industry Foundation for Culture, 2018)
"Toward the end of the Tokugawa shogunate, Mutsu Munemitsu was ousted from his home Kish?au-han as a result of his father's defeat in a power struggle. To avenge this, Mutsu bolstered his talent to become a man of "genius and learning in equal measure." He joined the Kobe Naval Training Center founded by Katsu Kaish?au and, later, Kaientai, a trading and shipping company and private navy founded and managed by Sakamoto Ry?aoma before the Meiji Restoration was accomplished. During the Meiji era, Mutsu fully exercised his extraordinary ability, including working to revise unequal treaties with Western powers as foreign minister. In his last days, he scrambled to end the First Sino-Japanese War; his efforts resulted in the signing of the Treaty of Shimonoseki with favorable terms for Japan. Mutsu also helped Japan ride out the subsequent wave of the Tripartite Intervention from Russia, France, and Germany. This book's author, a career diplomat himself, traces the footsteps of modern Japan's diplomacy by reviewing the philosophical and political journey of this extraordinary diplomat who protected the dignity of Japan as a modern nation throughout his professional life" -- United summary from book.
Father and son : at the apex of eighteenth-century culture -- Date Munehiro in exile (Jitoku-?ao) : intellectual pilgrimage of an Edo dignitary -- Meiji restoration : into the age of revolution and gun smoke -- Giant wings broken : the rise and fall of a Prussian-style military state -- A bush warbler in winter : involved in Tosa's adventure -- Burning the midnight oil again : study during imprisonment -- Burning the midnight oil a third time : in a Prussian-style constitution appropriate? -- The origins of Japanese democracy : building a modern nation-state -- The dawn of constitutional government : a Samurai democracy to be proud of -- First setback for the parliamentary democracy : bloody intervention in the election -- Revision of treaties : freedom from half a century of humiliation -- Rivalry on the Korean Peninsula : one imperialism vs. another -- The Donghak peasant rebellion : is Korea a tributary to Qing China? -- The eve of the first Sino-Japanese War : tenacity -- A war of diplomacy : keeping the Western powers at bay -- The Battle of Pungdo : dawn of an empire -- Japan sails to victory : China's strategic dilemma -- The final phase of the ware : a race against time -- The treaty of Shimonoseki : Li Hongzhang in Japan -- The Tripartite Intervention : an unavoidable concession -- Mutsu's death : fighting for democracy to the last.
"The original English translation is based on the paperback version of 'Mutsu Munemitsu to sono jidai,' published by PHP Institute, Inc. in 2003; first published in hardcover by the same publisher in 1999"--title page verso.
Includes bibliographical references.
Text in English.
Keywords: Mutsu, Munemitsu -- 1844-1897.; Diplomats -- Japan -- Biography; Japan -- Foreign relations -- 1868-1912.